Answer:
Step-by-step explanation:
first, we find the slope
slope = (y2 - y1) / (x2 - x1)
(-3,7)....x1 = -3 and y1 = 7
(9,-1)...x2 = 9 and y2 = -1
now we sub
slope(m) = (-1 - 7) / (9 - (-3) = -8 / (9 + 3) = -8 / 12 reduces to - 2/3
y = mx + b
slope(m) = -2/3
use either of ur points...I will use (-3,7)...x = -3 and y = 7
now we sub and find b, the y intercept
7 = -2/3(-3) + b
7 = 2 + b
7 - 2 = b
5 = b
so ur equation is : y = -2/3x + 5 <===
Answer:
![y=-\frac{1}{3}x+7](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B3%7Dx%2B7)
Step-by-step explanation:
we know that
If two lines are parallel then their slopes are equal
The equation of the given line is
![y=-\frac{1}{3}x+4](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B3%7Dx%2B4)
the slope is ![m=-\frac{1}{3}](https://tex.z-dn.net/?f=m%3D-%5Cfrac%7B1%7D%7B3%7D)
so
the slope of the parallel line to the given line is also ![m=-\frac{1}{3}](https://tex.z-dn.net/?f=m%3D-%5Cfrac%7B1%7D%7B3%7D)
Find the equation of the line that is parallel to the given line and passes through the point (6, 5)
we have
![m=-\frac{1}{3}](https://tex.z-dn.net/?f=m%3D-%5Cfrac%7B1%7D%7B3%7D)
![point\ (6,5)](https://tex.z-dn.net/?f=point%5C%20%286%2C5%29)
The equation of the line in point slope form is
![y-y1=m(x-x1)](https://tex.z-dn.net/?f=y-y1%3Dm%28x-x1%29)
substitute
![y-5=-\frac{1}{3}(x-6)](https://tex.z-dn.net/?f=y-5%3D-%5Cfrac%7B1%7D%7B3%7D%28x-6%29)
Convert to slope intercept form
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
isolate the variable y
![y-5=-\frac{1}{3}x+2](https://tex.z-dn.net/?f=y-5%3D-%5Cfrac%7B1%7D%7B3%7Dx%2B2)
![y=-\frac{1}{3}x+2+5](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B3%7Dx%2B2%2B5)
![y=-\frac{1}{3}x+7](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B3%7Dx%2B7)
XZ=XY+YZ
JL=JK+KL
use the trigonometric values table or unit circle to calculate the expression
Answer:
A i think
Step-by-step explanation:
5. y = -3 x - 8
6. y = - 1/2 x + 1